THE ROLE OF ORGANIZATIONAL CULTURE IN ENHANCING EMPLOYEE PERFORMANCE IN THE PUBLIC BANKING SECTOR - Pratiwi, Nurul; Halimah, Mas; Candradewini (International Journal of Cultural and Social Science, 2026)
This study aims to analyze the influence of organizational culture on employee performance in the public banking sector in South Sulawesi using a quantitative approach and SmartPLS analysis tools. Data was collected by distributing questionnaires to 100 respondents who were public banking employees in the region. The results of the analysis show that organizational culture has a positive and significant influence on employee performance, where the consistent application of organizational values can influence individual behavior and attitudes, thereby impacting on improved work performance.